2023
DOI: 10.1186/s41747-023-00331-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gadolinium-based contrast agents for MR cholangiography in saline, blood and bile: a phantom study

Abstract: Background We compared T1- and T2-weighted signal intensities of liver-specific (gadoxetate, gadobenate) and non-specific (gadoterate) gadolinium contrast agents (CAs) in a bile phantom. Methods In a phantom study, gadoxetate, gadobenate, and gadoterate were diluted in saline, blood, and bile at different concentrations (0, 0.25, 0.5. 1, 2.5, 5, 10, and 25 mM) and imaged in a 3-T magnetic resonance imaging (MRI) system using T1- and T2-weighted seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Potential sex and gender differences in OATP expression are poorly understood, and may impact the uptake of gadoxetate and gadobenate into the liver. This could influence the pharmacokinetics of gadoxetate particularly due to its high uptake by hepatocytes (about 50% of gadoxetate dose and 3–5% of gadobenate dose are taken up by hepatocytes). In preclinical studies with rats, differences in mRNA expression were not observed for liver OATP1. , A retrospective clinical study analyzed the PK of an endogenous substrate of OATP1B (Coproporphyrin I) in men and women and did not find differences between genders .…”
Section: Eliminationmentioning
confidence: 99%
“…Potential sex and gender differences in OATP expression are poorly understood, and may impact the uptake of gadoxetate and gadobenate into the liver. This could influence the pharmacokinetics of gadoxetate particularly due to its high uptake by hepatocytes (about 50% of gadoxetate dose and 3–5% of gadobenate dose are taken up by hepatocytes). In preclinical studies with rats, differences in mRNA expression were not observed for liver OATP1. , A retrospective clinical study analyzed the PK of an endogenous substrate of OATP1B (Coproporphyrin I) in men and women and did not find differences between genders .…”
Section: Eliminationmentioning
confidence: 99%